FEHÎM-İ KADÎM DÎVÂNI'NIN TAHLÎLİ - FELEK, ÖZGEN (Fırat Üniveristesi, 2007)
Bu çalışma, 17, yüzyıl Dîvân şairlerinden Fehîm-i Kadîm'in Dîvânı'nın tahlili ve şiirlerinde Sebk-i Hindî izleri üzerinedir. Sebk-i Hindî şairleri içinde zikredilen şairin şiirlerinde bu üslubun izleri incelenmiştir. Şairin hayatı, sanatı ve eserleri hakkında bilgi verildikten sonra, Fehîm Dîvânı Din-Tasavvuf, Toplum, İnsan ve Tabiat olmak üzere dört ana bölümde incelenmiş, şairin hayata ve yaşadığı döneme dair izlenimlerini şiirine nasıl yansıttığı araştırılmıştır. Sonuç olarak, öteden beri Sebk-i Hindî içinde ismi zikredilen şairin eseri detaylı bir şekilde incelenmiş ve Sebk-i Hindî içindeki yeri net bir şekilde ortaya konulmuştur

This study is based on the analysis of the poetry collection of 17th century poet Fehîm-i Kadîm. The characteristics of the Indian Style (Indian Style) have been examined in the poetry of Fehîm, who has been considered one of the noticed Ottoman poets influenced by the Indian Style. After providing information about the life story, work and the artistry of the poet, within four major chapters, which are entitled Religion-Mysticism, Society, Human Being, and Nature, his poetry collection was analyzed and how the poet reflected his observations about life and the time period in which he lived was examined. In conclusion, the poetry collection of Fehîm-i Kadîm who has been considered a Sabk-i Hindî poet was analyzed in detail and the place of the poet within the Indian Style was clearly stated.
Analysis of the poetry collection of Fehîm-i Kadîm
Keywords: Türk Dili ve Edebiyatı